2009
DOI: 10.3736/jcim20091213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yanggan Lidan Granule on insulin resistance in guinea pigs with induced cholesterol gallstones

Abstract: YGLDG may improve insulin resistance in guinea pigs with cholesterol gallstones by elevating GIR obviously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…LDG has been used as a routine treatment for gallstones for many years, and clinical studies have demonstrated that LDG can promote biliary excretion and litholysis ( 15 ). LDG is composed of 15 types of Chinese herbs, namely, oriental wormwood, hawthorn fruit, rice sprout, germinated barley, green orange peel, tangerine peel, medicated leaven, cyperus tuber, radish seed, perilla stem, turmeric root, bitter orange, pinellia tube, and Chinese honey locust fruit, which is based on the Chinese medicinal principle of smoothening liver function, dredging the gallbladder, harmonizing the stomach, and strengthening the spleen ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…LDG has been used as a routine treatment for gallstones for many years, and clinical studies have demonstrated that LDG can promote biliary excretion and litholysis ( 15 ). LDG is composed of 15 types of Chinese herbs, namely, oriental wormwood, hawthorn fruit, rice sprout, germinated barley, green orange peel, tangerine peel, medicated leaven, cyperus tuber, radish seed, perilla stem, turmeric root, bitter orange, pinellia tube, and Chinese honey locust fruit, which is based on the Chinese medicinal principle of smoothening liver function, dredging the gallbladder, harmonizing the stomach, and strengthening the spleen ( 23 ).…”
Section: Discussionmentioning
confidence: 99%